Edukasi dan Pendampingan Pembudidayaan Bawang Putih Lumbu Hijau di Dusun Jorong, Sembalun, Lombok Timur - -, Zuhdiyah Matienatul Iemaaniah; Bustan; Mulyati; Rika Andriati Sukma Dewi; Siska Ita Selvia; Joko Priyono; Lalu Bahrul Ilmi; Muh. Safrony Akmal (Jurnal Pengabdian Magister Pendidikan IPA, 2024)
The area of Mount Rinjani is developing rapidly as a vegetable and fruit farming area that supplies the needs of basic vegetable and fruit commodities. Garlic is one of the main agricultural commodities as the main seasoning in every dish. The Sumur Lembokek Farmers Group in Jorong Hamlet in Sembalun District, some of whose members grow garlic. The Sumur Lembokek Farmers Group in Sembalun District has often cultivated garlic, but farmers in this farmer group still experience obstacles, namely rotting of their onion bulbs. When the garlic plant is 50-70 days old after planting, the garlic begins to rot. The rot that occurs is always gradual from several plants, not simultaneously but within 20 days some plants will rot so that the harvest fails. Therefore, to help farmer groups in solving these problems, the community service team carried out educational activities and assistance in garlic cultivation which aimed to provide education and socialization related to good and correct garlic cultivation. This activity was carried out on July 10 and 16, 2024, which was located at the house of the Head of the Sumur Lembokek Group, which was attended by 15 members of the farmer group. The results of this activity provide enlightenment and solutions related to the problems experienced by using silicate-based fertilizers. In the continuation of the activity, cultivation activities are still ongoing and are in the trial stage of using silicate-based fertilizers to overcome the problem of rotting garlic bulbs.